Financial Development and Inclusive Growth : Attaining Shared and Sustainable Prosperity in Egypt - World Bank (Washington, DC, 2014)
Better functioning financial systems foster economic growth, poverty alleviation; moreover, a more equitable distribution of economic opportunities enhances overall economic development. It is critical that financial development leads to inclusive growth. This brings us to certain key questions: Who benefits from a better financial system? Does financial development induce an increase in per capita Gross Domestic Product (GDP) only because the very rich are getting even richer? Does finance expand economic opportunities for the bulk of society? Economic theory suggests that finance shapes the distribution of economic opportunities. The financial system affects the degree to which a person s economic opportunities are defined. It influences who can launch a new business venture and who cannot, who can acquire education and who cannot, who can live in a neighborhood that fosters the cognitive and non-cognitive development of their children and who cannot, who can pursue one s economic dreams and who cannot. A more competitive, better functioning financial system exerts a disproportionately positive impact on relatively low-income families. According to the extent that the financial system performs these functions well, economies tend to grow correspondingly faster. For example, when banks screen borrowers effectively and identify firms with the most promising prospects, this is a first step in boosting productivity growth. When financial markets and institutions mobilize savings from disparate households to invest in these promising projects, this represents a second crucial step in fostering economic growth. When financial institutions monitor the use of investments after financing firms and scrutinize their managerial performance, this is an additional, essential ingredient in boosting the operational efficiency of corporations, reducing waste and fraud, and spurring economic inclusivity. There is a robust positive relationship between financial development and both poverty alleviation and reduction in income inequality. It is not just that finance accelerates economic growth, which trickles down to the poor; rather, finance exerts a disproportionately positive influence on lower income households. Building on the finance and poverty connection, there is a direct link between finance and human welfare. When policy reforms foster the development of the financial system, financial services improve, accelerating economic growth, which ultimately leads to ending extreme poverty and boosting shared prosperity.